How Communication "Failed" or "Saved the Day": Counterfactual Accounts of Medical Errors. (December 2020) - Street, Richard L; Petrocelli, John V; Amroze, Azraa; Bergelt, Corinna; Murphy, Margaret; Wieting, J Michael; Mazor, Kathleen M
Communication breakdowns among clinicians, patients, and family members can lead to medical errors, yet effective communication may prevent such mistakes. This investigation examined patients' and family members' experiences where they believed communication failures contributed to medical errors or where effective communication prevented a medical error ("close calls"). The study conducted a thematic analysis of open-ended responses to an online survey of patients' and family members' past experiences with medical errors or close calls. Of the 93 respondents, 56 (60%) provided stories of medical errors, and the remaining described close calls. Two predominant themes emerged in medical error stories that were attributed to health care providers—information inadequacy (eg, delayed, inaccurate) and not listening to or being dismissive of a patient's or family member's concerns. In stories of close calls, a patient's or family member's proactive communication (eg, being assertive, persistent) most often "saved the day." The findings highlight the importance of encouraging active patient/family involvement in a patient's medical care to prevent errors and of improving systems to provide meaningful information in a timely manner.